The association of household food insecurity and HIV infection with common mental disorders among newly diagnosed tuberculosis patients in Botswana. Issue 4 (19th April 2022) - Wang, Qiao; Dima, Mbatshi; Ho-Foster, Ari; Molebatsi, Keneilwe; Modongo, Chawangwa; Zetola, Nicola M; Shin, Sanghyuk S
Abstract: Objective: To determine the association between food insecurity and HIV infection with depression and anxiety among new tuberculosis (TB) patients. Design: Our cross-sectional study assessed depression, anxiety and food insecurity with Patient Health Questionnaire (PHQ-9), Zung Anxiety Self-Assessment Scale (ZUNG) and Household Food Insecurity Access Scale, respectively. Poisson regression models with robust variance were used to examine correlates of depression (PHQ-9 ≥ 10) and anxiety (ZUNG ≥ 36). Setting: Gaborone, Botswana. Participants: Patients who were newly diagnosed with TB. Results: Between January and December 2019, we enrolled 180 TB patients from primary health clinics in Botswana. Overall, 99 (55·0 %) were HIV positive, 47 (26·1 %), 85 (47·2 %) and 69 (38·5 %) indicated depression, anxiety and moderate to severe food insecurity, respectively. After adjusting for potential confounders, food insecurity was associated with a higher prevalence of depression (adjusted prevalence ratio (aPR) = 2·30; 95 % CI 1·40, 3·78) and anxiety (aPR = 1·41; 95 % CI 1·05, 1·91). Prevalence of depression and anxiety was similar between HIV-infected and HIV-uninfected participants. Estimates remained comparable when restricted to HIV-infected participants. Conclusions: Mental disorders may be affected by food insecurity among new TB patients, regardless of HIV status.